2019
DOI: 10.3390/healthcare8010007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Performance Indicators for Hospital Management Using an Extended Hesitant Linguistic DEMATEL Approach

Abstract: Performance analysis is of great significance to increase the operational efficiency of healthcare organizations. Healthcare performance is influenced by numerous indicators, but it is unrealistic for administrators to improve all of them due to the restriction of resources. To solve this problem, we integrated double hierarchy hesitant fuzzy linguistic term sets (DHHFLTSs) with the decision-making trial and evaluation laboratory (DEMATEL) and proposed a DHHFL– DEMATEL method to identify key performance indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…In this study, we use FAHP to obtain the relative weights of criteria i (i ¼ 1, 2, …, k) and sub-criteria j (j ¼ 1, 2, …, n). Nevertheless, FAHP does not analyse the dynamic interrelations inherent to the healthcare scenario [51,52]. We therefore propose the integration of FAHP and FDEMATEL methods to address this limitation.…”
Section: The Combination Of Fahp and Fdematelmentioning
confidence: 99%
“…In this study, we use FAHP to obtain the relative weights of criteria i (i ¼ 1, 2, …, k) and sub-criteria j (j ¼ 1, 2, …, n). Nevertheless, FAHP does not analyse the dynamic interrelations inherent to the healthcare scenario [51,52]. We therefore propose the integration of FAHP and FDEMATEL methods to address this limitation.…”
Section: The Combination Of Fahp and Fdematelmentioning
confidence: 99%
“…However, the studies have shown that use of hybrid indicators in performance appraisal can caused better results. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, one of the criteria for measuring the success of organization and determining how to achieve its goal is organization's statistics and indices. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…The severity, occurrence, and detectability for each failure mode was estimated based on the levels indicated in Table 1. The RPN was calculated using Equation (1).…”
Section: Rpn = Severity (S) × Occurrence (O) × Detection (D)mentioning
confidence: 99%
“…It follows that it is necessary to reduce the operating costs through evaluation and improvement of internal hospital processes. Due to the growing demands for quality improvement and the increasing pressure from regulatory agencies, issues regarding how to provide high-quality hospital services and improve patient satisfaction have caught the attention of hospital administrators [ 1 , 2 ]. Specifically, an efficient hospital sterilization process (HSP) ensures that reusable medical devices (RMDs) are more rapidly available for healthcare activities.…”
Section: Introductionmentioning
confidence: 99%